Capacity Building Petugas Pendataan untuk Kepentingan Penetapan Pajak Bumi dan Bangunan Perdesaan dan Perkotaan - Eri Wahyudi; Dhian Adhetiya Safitra; Aniek Juliarin; Kristian Agung Prasetyo; Adhipradana Prabu Swasito; Edy Riyanto; Teguh Warsito; Hanik Susilawati Muamarah (Penerbit Goodwood, 2022)
Tujuan (Purpose): This program aims to identify the skill needs of the Kulon Progo Regency and improve the competence of the Kulon Progo Regency data collection officer or appraisers. Metode (Method): The method used to achieve the goal is to carry out a capacity building program. At the beginning of the program, we conducted a pre-test to identify the level of understanding. Then we provide online materials and practices. At the end of the program, we held a post-test to evaluate the implementation of capacity building. We use the real object of Yogyakarta International Airport so that participants can directly discuss the actual situation on the field. Hasil (Results): From the post-test results, we can see an increase in the knowledge of the officers. However, we have identified several regulatory instruments that Kulon Progo Regency does not yet have. Kesimpulan (Conclusions): From the results of this capacity building activity, we know there is a need for a sustainable capacity building program with an actual tax object.